STUDI ISLAM DENGAN PENDEKATAN TASAWUF MISTISEM ISLAM - Lukman Hakim Mustaqim, Aziz; Enong Fatonah, Mas; Maulana, Khamid; Hajam, Hajam; Shaumantri, Theguh (Berajah Journal, 2024)
The study of Islam with an approach to Sufi mysticism focuses on the spiritual dimension of Islam, emphasizing the pursuit of closeness to God through inner experiences such as dhikr and meditation. Sufism offers an approach that differs from the legal and social aspects of Islam, prioritizing unity with God and the purification of the soul. This research explores the history of Sufism, mystical experiences like fana and baqa, and critiques of Sufi practices from both traditional and reformist scholars. Additionally, Sufism is examined in the context of contemporary Islamic society, connecting it with psychology and philosophy to balance rational and spiritual aspects. This journal aims to provide insights into Sufism’s contribution to character formation and spirituality among Muslims, as well as its relevance in a modern, materialistic world